Influence of pyrazole on the photovoltaic performance of dye-sensitized solar cell with polyvinylidene fluoride polymer electrolytes - Senthil, R.A.; Theerthagiri, J.; Madhavan, J.; Arof, Abdul Kariem (Springer Verlag (Germany), 2016)
We investigate the influence of the pyrazole content on the polyvinylidene fluoride (PVDF)/KI/I2 electrolytes for dye-sensitized solar cells (DSSCs). The solid polymer electrolyte films consisting of different weight percentage ratios (0 20,30,40, and 50%) of pyrazole doped with PVDF/KI/I2have been prepared by solution casting technique using N,N- dimethyl formamide (DMF) as a solvent. The as-prepared polymer electrolyte films were characterized by various techniques such as Fourier transform infrared spectroscopy (FT-IR spectroscopy), differential scanning calorimetry (DSC), X-ray diffractometer (XRD), alternate current (AC)-impedance analysis, and scanning electron microscopy (SEM). The 40 wt% pyrazole-PVDF/KI/I2 electrolyte exhibited the highest ionic conductivity value of 9.52×10− 5 Scm− 1 at room temperature. This may be due to the lower crystallinity of PVDF and higher ionic mobility of iodide ions in the electrolyte. The DSSC fabricated using this highest ion conducting electrolyte showed an enhanced power conversion efficiency of 3.30% under an illumination of 60 mW/cm2 than that of pure PVDF/KI/I2 electrolyte (1.42%).